Colorimetric detection of Tritrichomonas foetus by a LAMP assay in preputial fluid and cryopreserved semen from bulls raised in Sonora, Mexico - Oroz-Rojo, Gustavo-Francisco; Aragón-López, Carlos-Eduardo; Flores-Encinas, Luis-Angel; Morales-Pablos, Marcela-Ivone; Urrea-Quesada, Alejandro; Torres-Simental, Jose-Florentino; Luna-Nevarez, Pablo; Leyva-Corona, Jose-Clemente (Revista Colombiana de Ciencias Pecuarias, 2025)
Background: Bovine trichomoniasis, caused by Tritrichomonas foetus, is a venereal disease that affects the reproductive efficiency of cattle, especially in extensive breeding systems. Infected bulls could spread the protozoan by artificial insemination if the semen is contaminated. The loop-mediated isothermal amplification (LAMP) is an alternative assay to detect genetic material of pathogens without the need to purify inhibitors contained in a biological sample. Objective: Detection of T. foetus in cryopreserved semen and genital fluids from bulls raised in Sonora Mexico by a colorimetric LAMP assay. Methods: The conditions for a colorimetric LAMP assay were standardized using PCR as analytical reference in order to detect T. foetus (crLAMP-TF). A total of 110 preputial samples were tested by crLAMP-TF. From positive males to T. foetus (TF+), seminal samples were collected, cryopreserved and tested by crLAMP-TF. Results: The crLAMP-TF assay was sensitive, and allow the visual detection at 35 min. without inhibitors purification of biological samples previous to DNA extraction. The 29.1% of the bulls were bTF+ and 27.3% of the thaws were contaminated. Conclusion: This survey confirms the presence of T. foetus in Sonora, Mexico and the ability of the protozoan to contaminate semen, which represents a potential risk of transmission during assisted reproduction programs by artificial insemination. The crLAMP-TF assay represents a viable alternative against traditional molecular techniques and its potential in the epidemiological surveillance of pathogens under field conditions.